(untitled) (E Global Congress, 2023)
This article gives information about role and importance of the service sector in the country’s national economy. Issues of improving the competitiveness of restaurant services have been studied.In this regard, advanced foreign experience is studied and the factors of ensuring competitiveness in catering enterprises are shown. There are also suggestions for improving the competitiveness of restaurant services.